法과 强制 그리고 現代的 傾向 - 文鍾旭(Moon Jong-Wook) (법학연구, 2003)
The legal Compulsion has been regarded as a essence of law. In fact, this view almost corresponds to the substance of law, and many well-known jurists have agreed to this view, too. But the legal compulsion should be founded voluntary observance all the way. Particularly in legal philosophy, it would be seriously kept watch the legal compulsion deviated from the reasonable legal level may arrive at the legal violence at all. Anyway, as the enlargement of legal function, the forms of legal compulsion are also changing in these day. So to speak, legal compulsion would not be able to gu따antee the success of lawmaking any more. Namely, the changed forms of legal compulsion in accordance with the enlargement of legal function might be able to gu따antee the success of lawmaking. Because the substantial realization of goal of lawmaking is more important than lawmaking guaranteed by traditional legal compulsion simply. Still the legal compulsion is extremely stern, if the goal of lawmaking would not be realized, what the lawmaking means would be nothing. Accordingly, the form of compulsion should be converted to benefiting or fostering compulsion. In short, as all citizens shall be assured of human dignity and worth, the law should be still in existence for the realization of ultimate legal value, and the legal compulsion should support the substantial realization of goal of lawmaking . KCI Citation Count: 0